2010
DOI: 10.1074/jbc.m110.168302
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Insights into the Roles of Amino Acid Residues in Ligand Binding for Two Closely Related Family 16 Carbohydrate Binding Modules

Abstract: Carbohydrate binding modules (CBMs) are specialized proteins that bind to polysaccharides and oligosaccharides. Caldanaerobius polysaccharolyticus Man5ACBM16-1/CBM16-2 bind to glucose-, mannose-, and glucose/mannose-configured substrates. The crystal structures of the two proteins represent the only examples in CBM family 16, and studies that evaluate the roles of amino acid residues in ligand binding in this family are lacking. In this study, we probed the roles of amino acids (selected based on CBM16-1/ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…AGE showed that the mutants K455A, E485A, and Q487A of CBM80 RfGH5 retained WT affinity for all of the ligands tested, which suggests that the predicted polar interactions between the protein and β-glycans have very little influence on affinity. These data are unusual among type B CBMs where direct polar interactions generally make an important contribution to ligand recognition (14,15). The data, however, are consistent with CfCBM2b-1, in which affinity is dominated by two tryptophans (16).…”
supporting
confidence: 62%
“…AGE showed that the mutants K455A, E485A, and Q487A of CBM80 RfGH5 retained WT affinity for all of the ligands tested, which suggests that the predicted polar interactions between the protein and β-glycans have very little influence on affinity. These data are unusual among type B CBMs where direct polar interactions generally make an important contribution to ligand recognition (14,15). The data, however, are consistent with CfCBM2b-1, in which affinity is dominated by two tryptophans (16).…”
supporting
confidence: 62%
“…S3 in the supplemental material). This observation may be akin to the fine-tuning demonstrated in a Caldanaerobius polysaccharolyticus family 16 CBM by mutating one polar residue (Q121 to E121) involved in hydrogen bonding with the ligand (47). The E545, K549, Q561, and K565 residues can also be found in four CBM3 modules from the related organisms C. kronotskyensis, C. saccharolyticus, C. obsidiansis, and Caldicellulosiruptor sp.…”
Section: Discussionmentioning
confidence: 92%
“…Single colonies were inoculated in 7 ml of LB medium supplemented with 100 g of ampicillin/ml and cultured for 10 h. The plasmids were extracted from the recombinant E. coli cells, and the inserts were sequenced (W. M. Keck Center for Comparative and Functional Genomics, University of Illinois) to confirm the presence of the desired mutation. Circular dichroism scans of mutated proteins were carried out using a J-815 CD spectropolarimeter (Jasco, Japan) equipped with a constant-temperature cell-holder as described in our previous report (47). Briefly, proteins (0.2 mg/ml) in a phosphate buffer (10 mM sodium phosphate [pH 7.0]) in a 1-mm quartz cuvette were kept at 25°C for 5 min before scanning.…”
Section: Methodsmentioning
confidence: 99%
“…Here we discuss the dynamics of Caldanaerobius polysaccharolyticus Man5B, an enzyme that cleaves both β-1,4 glucosidic and β-1,4 mannosidic linkages [ 5 ]. Man5B and Man5A, two glycoside hydrolase family 5 (GH5) enzymes from the same bacterium, were shown to act synergistically and at high temperature on enzymatic conversion of plant cell wall polysaccharides to fermentable sugars [ 5 , 6 ], a property that is highly desirable in the emerging biofuel industry [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%